Imatinib inhibits the regrowth of human colon cancer cells after treatment with 5-FU and cooperates with vitamin D analogue PRI-2191 in the downregulation of expression of stemness-related genes in 5-FU refractory cells. Issue 189 (May 2019) - Kotlarz, Agnieszka; Przybyszewska, Małgorzata; Swoboda, Paweł; Neska, Jacek; Miłoszewska, Joanna; Grygorowicz, Monika Anna; Kutner, Andrzej; Markowicz, Sergiusz
Graphical abstract: Highlights: Stemness-related genes are upregulated in human colon cancer cells which survived 5-FU treatment. Imatinib inhibits the regrowth of 5-FU-pretreated human colon cancer cells under normoxia and hypoxia. A combination of imatinib and PRI-2191 downregulates stemness-related genes in 5-FU refractory cells more efficiently than imatinib alone. PRI-1906 abolishes the effect of imatinib on gene expression in 5-FU-refractory HCT-116 cells undergoing renewal under normoxia. Imatinib cooperates with PRI-2191 interfering with colorectal cancer renewal in vitro following treatment with 5-FU. Abstract: Conventional cytotoxic drugs preferentially eliminate differentiated cancer cells but spare relatively more resistant stem-like cancer cells capable to initiate recurrence. Due to cancer cell plasticity, the stem-like phenotype can be also acquired by cancer cells refractory to treatment with cytotoxic drugs. We investigated whether drugs inhibiting receptor tyrosine kinases could be used to target human colon cancer cells initiating cancer regrowth following conventional cytotoxic treatment. The moderately differentiated cell line HT-29 and poorly differentiated cell line HCT-116 were exposed to 5-fluorouracil (5-FU). Cells that resisted the exposure to 5-FU were subsequently treated with imatinib or sunitinib. Both drugs reduced clonogenicity of 5-FU-refractory cells under normoxic and hypoxic culture conditions. The expression of numerous stemness-related genes was upregulated in cancer cells following the exposure to 5-FU, and remained at a high level in 5-FU-refractory cells undergoing renewal under normoxia, but decreased spontaneously under hypoxia. Imatinib downregulated the expression of stemness-related genes in cells undergoing renewal under normoxia. A combination of imatinib with PRI-2191, an analogue of 1, 25-dihydroxyvitamin D3, downregulated stemness-related genes in HCT-116/5-FU cells more efficiently than imatinib alone. A synthetic analogue of 1, 25-dihydroxyvitamin D2 (PRI-1906) abolished the effect of imatinib on gene expression in HCT-116/5-FU cells undergoing renewal under normoxia. Sunitinib promoted shift of phenotype of HT-29/5-FU cells undergoing renewal toward stem-like one. It suggests that the phenotype shift toward stemness induced by sequential sunitinib treatment following 5-FU treatment could increase a risk of cancer recurrence. In contrast to sunitinib, imatinib could be used both to interfere with cancer regrowth after conventional chemotherapy and to downregulate the expression of stemness-related genes in residual colon cancer cells capable to initiate cancer recurrence. The findings suggest that imatinib could also be combined with vitamin D analogue PRI-2191 to prevent recurrence more efficiently than imatinib alone and to compensate for vitamin D deficiency resulting from imatinib treatment.